KONSEP TAFAQQUH FIDDĪN DALAM SISTEM PENDIDIKAN PESANTREN (KAJIAN AL-QURAN SURAT AT-TAUBAH AYAT 122) - Akit, Usman; Fatkhurrohman, Fatkhurrohman; Nasokah, Nasokah (DAS Institute, 2023)
This This research aims to: This research aims to 1) find out the contents of the Al-Qur'an, Surah At-Taubah verse 122, 2) find out the concept of Tafaqquh Fiddīn in the Islamic boarding school education system which is related to Surah At-Taubah verse 122, 3) find out the contextualization of the concept Tafaqquh Fiddīn in Islamic boarding school education in the modern era. This research uses qualitative research in field form. By using primary data sources directly through books, journals, etc., and secondary data, namely indirect sources through observation, interviews and documentation. So the data collection technique is carried out using 1) documentation study techniques, and 2) searching for data through online media, according to the search for materials related to research, then continuing with specific data. Data analysis uses content analysis and discourse analysis methods. The research results show that the Al-Qur'an Surah At-Taubah verse 122 explains the completeness of the laws relating to struggle. Namely, the law seeks knowledge and deepens religion according to what has been implemented in the Islamic boarding school education system. Where a student who is in Islamic boarding school is required to absorb as much religious knowledge as possible in the hope that one day after graduating from Islamic boarding school, what he has learned in Islamic boarding school can be put into practice, utilized and devoted to society, so that he can gain useful knowledge, blessings and blessings. from the community.